1995
DOI: 10.1073/pnas.92.20.9161
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of vinculin genes in F9 and embryonic stem cells changes cell morphology, adhesion, and locomotion.

Abstract: Vinculin, a major constituent of focal adhesions and zonula adherens junctions, is thought to be involved in linking the microfilaments to areas of cell-substrate and cell-cell contacts. To test the role of vinculin in cell adhesion and motility, we used homologous recombination to generate F9 embryonal carcinoma and embryonic stem cell clones homozygous for a disrupted vinculin gene. When compared to wild-type cells, vinculin-mutant cells displayed a rounder morphology and a reduced ability to adhere and spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
158
1
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 36 publications
13
158
1
2
Order By: Relevance
“…The actin cytoskeleton interacts with the extracellular matrix and intracellular molecules via the focal adhesion. The focal adhesion contains proteins such as tensin and vinculin (Coll et al, 1995) which are thought to also have tumor suppressor properties. Focal adhesion proteins are also key regulators of some signal transduction events (Weisberg et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The actin cytoskeleton interacts with the extracellular matrix and intracellular molecules via the focal adhesion. The focal adhesion contains proteins such as tensin and vinculin (Coll et al, 1995) which are thought to also have tumor suppressor properties. Focal adhesion proteins are also key regulators of some signal transduction events (Weisberg et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise biological function of vinculin is not fully understood yet, a variety of elegant studies has shown that vinculin is important in the organisation and maintenance of cell-contact architecture. Disruption of the vinculin gene leads to embryonic death in C. elegans [5] and to an altered adhesion and motility in F9 cells [6,7]. Similarly, cell adhesion is disturbed in cultered fibroblasts microinjected with antibodies against vinculin [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Vinculin plays a central role in the mechanical coupling of integrins to the cytoskeleton as well as in related control of cytoskeletal mechanics, cell shape, and motility (13)(14)(15)(16). Talin is responsible for a conformational change of integrins to an active state, and it also links the receptor to the actin cytoskeleton (17)(18)(19)(20).…”
mentioning
confidence: 99%